Chronicle. (Appalachian Journal)
This section offers a chronology of events in the U.S. The closing of the Hazard bureau of the "Louisville Courier-Journal" was covered by the "New York Times." This won the newspaper a Pulitzer Prize for public service. Robert L. Dennison, the mine foreman of the Sago mine where 12 miners died in January 2006, was indicted by a federal grand jury. Several directors of governing board of the Museum of Appalachia had decided to resign over conflicts with John Rice Irwin, the founder of the museum. Based on data from the National Center for Education Statistics and the U.S. Census Bureau, Hispanic enrollment has increased in rural public schools by 136 percent.